(untitled) (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article analyzes the development of Uzbekistan’s foreign economic activity and the importance of attracting investments. The article discusses Uzbekistan’s foreign trade policy, the urgent issues related to attracting foreign investments, and the external economic relations necessary for economic growth and sustainable development. It examines the impact of investments on the economy, how they can benefit Uzbekistan as a country emerging from an economic crisis, the role of introducing new technologies, modernizing production sectors, and creating new jobs. The article also provides information about the favorable conditions created in Uzbekistan for attracting investments, government programs, and the importance of cooperation with international organizations.